2003
DOI: 10.1021/ja034608u
|View full text |Cite
|
Sign up to set email alerts
|

XMCD for Monitoring Exchange Interactions. The Role of the Gd 4f and 5d Orbitals in Metal-Nitronyl Nitroxide Magnetic Chains

Abstract: We report here the X-ray magnetic circular dichroism (XMCD) study at the Gd M(4,5)- and L(2,3)-edges of two linear magnetic chains involving Gd(III) cations bridged by nitronyl nitroxide radicals. This spectroscopy directly probes the magnetic moments of the 4f and 5d orbitals of the gadolinium ions. We compare macroscopic magnetic measurements and local XMCD signals. The M(4,5)-edges results are in agreement with the J values extracted from the fits of the SQUID magnetic measurements. The L(2,3)-edges signals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…Experimentally it has been found that the Gd(III) 5d orbitals have no significant role on the next-nearest neighbour interaction in the polynuclear complexes. 50 The possible involvement of other orbitals, particularly the 6s, on the next-nearest neighbour interaction is an attractive idea and we are currently working on this issue.…”
Section: Discussionmentioning
confidence: 99%
“…Experimentally it has been found that the Gd(III) 5d orbitals have no significant role on the next-nearest neighbour interaction in the polynuclear complexes. 50 The possible involvement of other orbitals, particularly the 6s, on the next-nearest neighbour interaction is an attractive idea and we are currently working on this issue.…”
Section: Discussionmentioning
confidence: 99%
“…However, since other key works on XMCD of Gd have focused on the Gd M 5 edge, the relationship between the sign of the M 5 and L 3 dichroic edges and the direction of the magnetic moment needs to be briefly discussed. First, it was established in previous studies of ferromagnetic Gd that when the magnetization was aligned with the field, the sign of the dichroic spectrum at the M 5 edge was negative and at the L 3 edge was positive [48][49][50]. Therefore, for the Gd L 3 edge, the dichroic spectrum is positive when the Gd magnetic moment is positively aligned with the magnetic field, and the spectrum is negative when the Gd moment is antiparallel to the applied magnetic field.…”
mentioning
confidence: 96%
“…Figure presents the Gd M 4,5 and Mn L 2,3 edge XAS and XMCD spectra of the Mn-doped β-NaGdF 4 sample at T = 6.5 K. The Gd M 5 edge exhibits a large dichroic signal (−33 ± 1%) at 1184.2 eV of a negative sign and a characteristic Gd 3+ multiplet structure . The multiplet structure on the L-edges confirms the Mn 2+ valence state since higher manganese valences exhibit significantly broader features at the L 2,3 resonances, which are also shifted to higher photon energies. , The XMCD signal of −28 ± 2% at the L 3 edge (638.8 eV) has a negative sign as the XMCD signal of the gadolinium M 5 edge (cf.…”
Section: Results and Discussionmentioning
confidence: 83%